Micro, small and medium enterprise upgrading in low- and middle-income countries: a literature review - Caroline Reeg (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
Within the private sectors of low- and middle-income countries exists a significant productivity gap between a small number of highly productive large- and medium-sized enterprises and a large number of uncompetitive micro and small enterprises in backward industries. In fact, often the size segment of micro and small enterprise (MSEs) accommodates nearly all low-productivity businesses. These businesses are usually run by a single person or include a few family members as employees. More, these are typically located in traditional and informal markets characterized by low wages and unskilled labour. In order to boost their productivity and their job-creation potential MSEs need to initiate upgrading processes by which they incrementally improve the quality of their products, increase their human capital, adopt new technologies and enhance their specialisation and inter-firm linkages. However, a large amount of empirical studies documents that most MSEs in developing countries do not upgrade their businesses to the next level of productivity, assets and employment. Rather the majority of firms stagnates, closes down and exits the market. This discussion paper presents and discusses the questions as of which factors constrain and/ or promote micro and small enterprise upgrading in low- and middle-income countries. In this paper enterprise upgrading is defined as enterprise growth triggered by firm-level innovation. By combining different strands of literature this review intends to contribute to a clearer and more comprehensive understanding of what drives enterprise development and upgrading. Adopting a bird's eye perspective, empirical evidence on four groups of determinants is systematically reviewed. This includes factors that are associated with features internal to the firm, such as entrepreneur characteristics (1) and firm characteristics (2), as well as features external to the firm, such as the role of social and inter-firm networks (3) and the wider business environment (4). The paper argues that though an immense body of empirical work has been generated there is no clear trend in the literature on the question as of what determines enterprise upgrading. Indeed, due to the very idiosyncratic and cumulative nature of enterprise development there will be no universal `recipe' for enterprise development. However, in studying MSE enterprise upgrading it is crucial not to rely on mono-causal explanations , but to identify virtuous `combinations of success', meaning factors that in combination facilitate MSE upgrading. Naturally, these factor combinations can be quite different depending on the external institutional environment, the market structure and opportunities, as well as many more factors associated with the entrepreneur himself and his networks at hand. While the currently prevailing perspective in enterprise development highlights the positive contribution of market forces to establish an external business environment that is conducive to private sector development and enterprise upgrading this paper suggests that factors associated with the entrepreneur and his firm are underestimated. Factors such as the education and work experience of the entrepreneur as well as the enterprise's motivation and ability to develop tailored strategies for coping with the imperfections of the entrepreneurs' environment matter more than current perceptions suggest.
Keywords: 330; Strukturwandel; wirtschaftliche Entwicklung und Beschäftigung